PENGARUH PENDAPATAN ASLI DAERAH, PENGELUARAN DAERAH, DAN JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI: Studi Empiris Pada Pemerintah Kabupaten/Kota Di Lingkungan Provinsi Jawa Tengah Tahun 2018-2020 - Aris Munandar (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2023)
This research aims to analyze the effect of regional original income, regional expenditure, and population on economic growth in Regency/City Governments in the Province of Central Java. Central Java Province is experiencing fluctuating economic growth but its growth rate is relatively low compared to other provinces in Java Island. This research is a descriptive statistical-research. The research was conducted in 35 regencies/cities in Central Java Province using time series secondary data from 2018 – 2020 supported by library research. The data analysis technique in this study was multiple linear regression which was processed using SPSS 22 software. The results of the research show that there is no effect of regional original income on economic growth. Meanwhile, government spending in the form of direct spending and indirect spending as well as population shows a positive and significant impact on economic growth